Urban and regional planning - Hall, Peter 1932-2014; Tewdwr-Jones, Mark 1968- (Routledge, Taylor & Francis Group, 2020)
This is the sixth edition of the classic text for students of geography and urban and regional planning. It gives an historical overview of the changes in cities and regions and in the development of the theory and practice of planning throughout the 20th and 21st centuries.The extensively revised edition now incorporates new material on European issues, as well as updated country-specific sections and the impact of recession. Specific references are made to the most important British developments in recent times, including new towns, neo-liberalism, the devolution to Scotland, Wales and Northern Ireland, and to cities and combined authorities, the role of infrastructure and high-speed rail, the impact of austerity, neighbourhood planning, Brexit and the continual story of the north–south divide. A chapter on United States planning discusses the continuing trends of urban dispersal and social polarisation, the treatment of climate change, the rise of edge cities and the decline of rustbelt cities, as well as initiatives in new urbanism, land use planning and transportation policies. Finally, the book looks to discuss the main issues that are likely to impact on future forms of planning in the 2020s, including digitisation, automation, sustainability and social polarisation.Urban and Regional Planning will be invaluable to undergraduate as well as postgraduate Planning students. It will prove useful in a variety of built environment areas such as Architecture, Landscape Architecture, Urban Design, Real Estate, where planning is taught
Keywords: Geschichte 1800-1990; Raumordnung; Regionalplanung; Stadtplanung; Geschichte